Biomaterials and heart recovery: cardiac repair, regeneration and healing in the MCS era: a state of the “heart” - Di Franco, Sveva; Amarelli, Cristiano; Montalto, Andrea; Loforte, Antonio; Musumeci, Francesco (Journal of Thoracic Disease, 2018)
Regenerative medicine is an emerging interdisciplinary field of scientific research that, supported by tissue engineering is, nowadays, a valuable and reliable solution dealing with the actual organs shortage and the unresolved limits of biological or prosthetic materials used in repair and replacement of diseased or damaged human tissues and organs. Due to the improvements in design and materials, and to the changing of clinical features of patients treated for valvular heart disease the distance between the ideal valve and the available prostheses has been shortened. We will then deal with the developing of new tools aiming at replacing or repair cardiac tissues that still represent an unmet clinical need for the surgeons and indeed for their patients. In the effort of improving treatment for the cardiovascular disease (CVD), scientists struggle with the lack of self-regenerative capacities of finally differentiated cardiovascular tissues. In this context, using several converging technological approaches, regenerative medicine moves beyond traditional transplantation and replacement therapies and can restore tissue impaired function. It may also play an essential role in surgery daily routine, leading to produce devices such as injectable hydrogels, cardiac patches, bioresorbable stents and vascular grafts made by increasingly sophisticated biomaterial scaffolds; tailored devices promptly fabricated according to surgeon necessity and patient anatomy and pathology will hopefully represent a daily activity in the next future. The employment of these devices, still far from the in vitro reproduction of functional organs, has the main aim to achieve a self-renewal process in damaged tissues simulating endogenous resident cell populations. In this field, the collaboration and cooperation between cardiothoracic surgeons and bioengineers appear necessary to modify these innovative devices employed in preclinical studies according to the surgeon’s needs.